Afetividade e participação na metrópole: uma reflexão sobre dirigentes de ONGs da cidade de Fortaleza - Brandão, Israel Rocha (2008)
This study discusses social participation and affectivity among leaders of nongovernmental organizations (NGOs) at the city of Fortaleza. It aims to debate the understanding of how the process of participation of these citizens occurs, as well as its relationship with the issue of the affectivity, focusing on the relationship of these leaders with their respective organizations. The relevance of the work is based on the striking presence of these institutions in the current society and the existing divergences around their role as emancipatory institutions. The method of research involved some visits to the NGO´s physical and social spaces, and several interviews with its main leaders as well. The founding managers of five NGOs from Fortaleza had been heard headquartered. These NGOs have several areas of activity. All the involved institutions in the research are affiliated to the Brazilian Association of NGOs (ABONG), considering the rigorous criteria for admission. The theoretical approach of this writing is based, mainly, in the theories of T. Adorno, L. S. Vygotsky and B. Espinosa, whose considerations invite the researcher into a critical vision of the current society and a positive examination of the affectivity phenomenon. The main results reinforce the relevance of the family, as a setting for construction of participatory citizens, as well as the importance of the contact with other stakeholders´ institutions, such as universities, the political parties and the church. Moreover, a kind of modification has been observed in the ethical frameworks of these citizens toward to less ideological and religious understanding of the society or more plural and humanists visions of the human being